True or false?: activations of language-related areas in patients with disorders of consciousness - Kotchoubey, Boris; Yu, Tao; Mueller, Friedemann; Vogel, Dominik; Veser, Sandra; Lang, Simone (Current pharmaceutical design, 2014)
Twenty-nine patients with Unresponsive Wakefulness Syndrome (UWS), 26 patients in Minimally Conscious State (MCS), and 21 healthy control individuals matched in age and social environment (patients' relatives) were presented with 80 short sentences half of which were factually correct, and the other half factually incorrect. The diagnosis was made on the basis of repeated neurological examinations as well as the standardized assessment using a Coma Recovery Scale-Revised (CRS-R). fMRI blood oxygen level dependent signal was recorded in an event-related design time-locked to the end word of the sentences. In the contrast "incorrect-minus-correct" significant activations in the relevant brain regions were obtained in 17 (81%) controls and in 16 (29%) patients. Among patients, the 16 responders had a significantly longer time since accident than the 39 non-responders. Responders and non-responders did not differ in terms of the diagnosis (UWS vs. MCS), age, CRS-R score, or the degree of brain atrophy. The data concur with the results of several earlier studies on UWS/MCS patients, with the difference that the critical stimuli in those studies were semantically incongruent or ambiguous propositions rather than factually false ones in the present experiment. The hypothesis is discussed that the differential response of brain language areas to factually correct and incorrect statements does not require conscious perception of the statements.